Impact Assessment of Different Polymers on Physicochemical Properties of Ibuprofen Loaded Solid Dispersions - Ferdousy, Sonia; Sajeeb, BK; Yeasmin, Shahida; Faroque, ABM (Dhaka University Journal of Pharmaceutical Sciences, 2018)
In the present study, solid dispersions of ibuprofen were prepared to improve aqueous solubility of ibuprofen. A series of formulations were prepared where PEG 6000 with polymers named PVP K30, cross PVP, poloxamer 237, HPMC ASLF, pregelatinized starch, Na-CMC, Eudragit L100, and kollidon IR were used in different ratios. Among 41 formulations, solid dispersions of ibuprofen in PEG 6000 with each of PVP K30, poloxamer 237, and Na-CMC at ratio of 2:9:7 revealed improved solubility of 952.73 ± 1.31, 878.18 ± 0.97, and 1263.64 ± 1.58 μg/ml, respectively. The physicochemical properties of these preparations were ascertained by FTIR, SEM, DSC, and particle size analyses. FTIR spectrum showed absence of chemical interactions and physical compatibilities between ibuprofen and polymers were confirmed by DSC. Disappearance of individual surface properties in solid dispersions were revealed by SEM studies, which indicated the formation of effective preparations. On the other hand, particle size analysis showed reduction in particle size of ibuprofen from solid dispersions that demonstrated solubility enhancement of ibuprofen. The above studies suggested that solid dispersions of ibuprofen in PEG 6000 at ratios of 2:9:7 with each of PVP K30, poloxamer 237, and Na-CMC were found to be effective to improve aqueous solubility. Dhaka Univ. J. Pharm. Sci. 17(2): 183-190, 2018 (December)